2015
DOI: 10.4172/2329-8731.1000122
|View full text |Cite
|
Sign up to set email alerts
|

HBV Serological Profiles and Vaccination Status among Healthcare Workers in Istanbul, Turkey

Abstract: Introduction: The aim of this study is to determine the hepatitis B serological profiles, vaccination status, and prevalence of needlestick injuries (NSI) among HCWs in a tertiary hospital in Istanbul, Turkey.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Significantly higher vaccination coverage was found for medical doctors, pharmacists, first degree holders, master degree holders, and unmarried health professionals than their equivalents in the group. The presence of significant association between type of profession and vaccination status is also reported by so many studies [12, 13, 25, 28, 29]. The study done by Kathy et al reported that more than high school education has significantly higher vaccination coverage [14].…”
Section: Discussionmentioning
confidence: 82%
“…Significantly higher vaccination coverage was found for medical doctors, pharmacists, first degree holders, master degree holders, and unmarried health professionals than their equivalents in the group. The presence of significant association between type of profession and vaccination status is also reported by so many studies [12, 13, 25, 28, 29]. The study done by Kathy et al reported that more than high school education has significantly higher vaccination coverage [14].…”
Section: Discussionmentioning
confidence: 82%